ANALISIS TINGKAT ADOPSI PETANI DALAM PENERAPAN SISTEM TANAM JAJAR LEGOWO DAN PENGARUHNYA TERHADAP PENDAPATAN PETANI DI KECAMATAN INDRALAYA KABUPATEN OGAN ILIR - Kuswantinah (Sekolah Tinggi Ilmu Ekonomi (STIE) Aprin, 2021)
This research aims to determine (1) the technology adoption rate of Jajar Legowo planting system in Indralaya District of Ogan Ilir Regency, (2) the correlation between farmer's adoption rate with production for jajar legowo planting system implementation in Indralaya District of Ogan Ilir Regency and (3 ) income comparison between jajar legowo planting system and traditional planting system. This research took place from July 2017 to February 2018 in Indralaya District Ogan Ilir Regency. The method used in this research was survey; by interviewing 50 farmers as respondents (25 people who apply the jajar legowo planting system and 25 people who apply the traditional planting system). Data was processed and analyzed in the form of frequency table / tabulation and presented descriptively. The total score of jajar legowo technology implementation was analyzed with descriptive statistic. To see the correlation of adoption rate and income received by farmers, quantitative data processing is done by using nonparametric statistical analysis, which means this research is using simple linear regression analysis test. The results showed: 1) the technology rate for jajar legowo planting was high, starting from the seeds selection, soil processing, seeding, planting, maintenance, harvesting until postharvest. 2) There is a positive relationship in technology rate between jajar legowo system and traditional planting system, which means that if the technology rate was high , then the rice production will also high, which lead to the optimum limit. 3) Descriptively, the income between farmers who plant with jajar legowo planting system and farmers who plant with traditional planting system is different. Statistical test results showed significant differences between farmers who plant with jajar legowo system and farmers who plant with traditional planting system.